FAPb1−xSnxI3 mixed metal halide perovskites with improved light harvesting and stability for efficient planar heterojunction solar cells. Issue 19 (26th April 2017) - Liu, Jiang; Wang, Gang; Song, Zhen; He, Xulin; Luo, Kun; Ye, Qinyan; Liao, Cheng; Mei, Jun
Abstract : FA-based perovskite devices with reduced Pb contents were prepared. Abstract : Organic–inorganic halide perovskites possess excellent chemical, optical, and electronic properties that make them attractive for next-generation solar cells. An important target for the further improvement of perovskite-based solar cells is to eliminate or reduce the use of the heavy metal lead. Herein, we systematically investigated the performance of FAPb1− x Sn x I3 mixed metal halide perovskites. The addition of Sn led to the stabilization of the perovskite phase and the low temperature of 100 °C was enough to result in the formation of the perovskite phase. The efficiency of the solar cell fabricated in this study is over 10% at x = 0.5, owing to the improved light harvesting in spite of the reduced open voltage. As more Sn was added, the device performance gradually deteriorated. Importantly, we performed stability tests under white light illumination and demonstrated that the FASn0.5 Pb0.5 I3 material might be intrinsically stable in a nitrogen environment. These results show that the device based on the FASn0.5 Pb0.5 I3 absorber without encapsulation retained over 85% of the initial efficiency for 100 h in nitrogen, indicating that a highly efficient perovskite solar cell with reduced Pb content and long-term stability could be realized.